Contingent Capital : Economic Rationale and Design Features - Pazarbasioglu, Ceyla (Staff Discussion Notes; Staff Discussion Notes, 2011)
The causes of the global financial crisis were multi-faceted but revealed still unresolved weaknesses in national and international financial oversight and resolution frameworks. In particular, many governments in the crisis-hit countries had to provide unprecedented levels of support to contain the crisis and protect financial stability. These interventions have not only contributed to a significant increase in sovereign exposures but, in many countries, they have also risked weakening market discipline and worsening moral hazard.